PERANCANGAN APLIKASI PEMBELIAN BAHAN BAKU PRODUK KALENGAN PADA PT. TOBA SURIMI INDUSTRIES BERBASIS ANDROID - Fierdaus Feornado; Charles Jhony Mantho Sianturi (Bajang Institute, 2022)
PT. Toba Surimi Industries is a company engaged in the production of canned food sales. The problems faced by PT. Toba Surimi Industries so far is the process of purchasing raw materials this is done manually, namely the purchasing department purchases materials standard with Via Call so it takes quite a long time to implementation of purchasing raw materials from canned food. Purchase process manual canned food raw materials result in the purchasing process takes a long time and reports on the purchase of raw materials obtained is less accurate. Therefore we need a system that can help companies and customers to carry out the process of purchasing materials raw materials and tariffs for raw materials will be available automatically on the system to be designed. The system that the author proposes is Android. By using two hardware, namely Android and laptops. Android is an Operating System based on Linux which is used for smartphones and tablets. Android is open source and also Android provides an open platform for users developers to create or develop their own applications